Who liberalizes high-skilled immigration policy and when? Partisanship and the timing of policy liberalization in 19 European states. Issue 4 (16th March 2021) - Kolbe, Melanie
ABSTRACT: This article investigates the timing of HSI policy liberalization in Europe by focusing on the role of government partisanship in overcoming diverging pressures for and against greater openness. Using event history analysis to analyse changes in HSI policy in 19 European states from 1999 to 2011, this article finds that having right-leaning governments significantly accelerated HSI policy liberalization, while having left-leaning governments delayed it. The findings suggest that skilled immigration is not driven only by labour market dynamics but also by government partisanship. Moreover, the article sheds light on why right-wing parties, in contrast to their usual tendency to champion restrictive immigration policies, may pursue policy liberalization in the case of HSI.